1998
DOI: 10.1111/j.1600-0447.1998.tb10084.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated use of psychiatric emergency out‐patient services among new patients: a 3‐year follow‐up study

Abstract: The aim of this study was to examine repeated use of psychiatric emergency out-patient services during the second and third years after the first contact. A 1-year treated incidence cohort of 537 new patients was studied in the Department of Psychiatry in Oulu, Finland. Repeat users were defined as patients belonging to the upper 10th percentile of the emergency out-patient contacts. The median of emergency out-patient contacts among repeaters was 4. The repeaters constituted 8% of the cohort and they used 65%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 10 publications
4
47
1
1
Order By: Relevance
“…In this study, the following variables were found to predict frequent attendance: male; previous multiple hospital admissions; planned outpatient contacts; and repeated outpatient contacts. 15 The Australian scenario is scarcely described. An analysis of 500 frequent attenders over a 6-year period at an Australian inner-city ED found that 26.5% had primary psychiatric or altered conscious states due to drugs and alcohol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, the following variables were found to predict frequent attendance: male; previous multiple hospital admissions; planned outpatient contacts; and repeated outpatient contacts. 15 The Australian scenario is scarcely described. An analysis of 500 frequent attenders over a 6-year period at an Australian inner-city ED found that 26.5% had primary psychiatric or altered conscious states due to drugs and alcohol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This literature has identified predictors of repeated ED visits for mental health reasons including several socio-demographic, diagnostic and service use characteristics including: male gender [16,17], younger age [3,12,17,18], black or Hispanic race [12], unemployment [19,20], low income [3,17,18,21], homelessness [21,22], living alone [23], lacking social support [22], schizophrenia [3,12,18,20], psychosis [17,20], personality disorder [19,22,25], substance abuse [12,17,20,25], developmental delay [22], prior hospitalizations [21,22,24], history of detoxification [22], recent and increased use of outpatient treatment [21], current psychiatric treatment [25], and a history of incarceration [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some have defined frequent visits as more than two above the mean standard deviation (1,2), and some have used the upper tenth percentile of the sample (4). Others have defined frequent visits as one visit (3) or six visits (2,7) per year, four visits in a quarter (2), or at least six visits in six years (11).…”
mentioning
confidence: 99%
“…Previous studies have indicated that 2% to 18% of adult patients who repeatedly visited psychiatric emergency services generated 21% to 65% (1)(2)(3)(4)(5) of the total clinical activity in these settings. Recurrent use of emergency services is a significant cost burden (6,7).…”
mentioning
confidence: 99%